Effect of massage therapy on pain and quality of life in dogs: A cross sectional study. (13th June 2021) - Riley, Lisa M.; Satchell, Liam; Stilwell, Lisa M.; Lenton, Natalie S.
Abstract: Background: Clinical canine massage involves muscle tissue manipulation and fascial release techniques to rehabilitate injured soft tissues. Quantitative efficacy data are lacking. This cross‐sectional study aimed to determine how dogs respond to canine massage therapy practiced by Canine Massage Guild UK practitioners. Methods: In 2018, case notes from a convenience sample of 527 dogs were shared, with permission from owners, by a self‐selected sample of 65 practitioners. Changes in number and severity of issues for five pain indicators (gait, posture, daily activity, behaviour, performance) and quality of life score, reported by owner and practitioners, were investigated. Results: Significant reductions in reported pain severity scores were recorded for all pain indicators over successive treatments ( p < 0.001), with each treatment causing further significant reduction in pain severity. Number of pain indicators recorded over successive treatment sessions remained constant, in keeping with a cohort presenting with degenerative disease and chronic pain. All dogs and diagnostic variables responded similarly. Post‐treatment a dog was significantly more likely to have a 'positive' quality of life. Conclusions: This cross‐sectional study indicates canine massage therapy may effectively reduce myofascial and musculoskeletal pain severity reported by owners and practitioners associated with gait, posture, behavioural and performance issues and reduction in daily activities. Although this is not a double‐blind trial, and there is no control group, this study suggests massage therapy may be a valid treatment for myofascial and musculoskeletal pain typically derived from muscular injuries, arthritis/other orthopaedic conditions.